Comparative analysis of lily responses to elevated salinity in irrigation water: Effects on physiology, anatomy, and postharvest flower quality - Yahia A. OTHMAN; Tala S. A’SAF; Jamal Y. AYAD; Malik G. AL-AJLOUNI (Notulae Botanicae Horti Agrobotanici Cluj-Napoca)
Saline water irrigation presents a significant challenge in agriculture, especially in regions with water scarcity and soil salinity. Lilies are economically significant ornamental plants renowned for their aesthetic value and commercial importance. This study aims to evaluate the effects of saline water irrigation on lily anatomy, physiology, and postharvest flower quality. Three NaCl salinity levels with varying electrical conductivities (EC) (control 0.65, 3, and 6 dS m-1) were applied to three hybrid lilies (Lilium × elegans): fragrant Orienpet (‘Maytime’, white), non-fragrant Longiflorum-Asiatic (‘Pavia’, yellow), and ‘Fangio’ (pink).